Correlation between brainstem evoked response audiometry with other audiological tests in different types of hearing loss - Shah, Hemal; Kharadi, Pramod; Patel, Krunal; Jha, Sushil; Singh, Abhishek Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Brainstem evoked response audiometry (BERA) is most specific and sensitive test for brain stem dysfunction. It is most important objective method for evaluating peripheral auditory system in neonates, infants, sedated and comatose patients and other person who doesn’t understand the language. Objective of the study was to evaluate correlation BERA with other audiological tests in different types of hearing loss as well as to study variations of wave forms in different types of hearing loss. Methods: Patients underwent a complete ENT check up to rule out any actively discharging gears, wax, infection or any middle ear problems. Different audiometric tests: pure tone audiometry (PTA), distortion product otoacoustic emissions, auditory steady-state response (ASSR) and BERA were applied to the patients. Results: The majority of the patients (32 cases) belonged to the age group of 0-5 years. Maximum cases were of sensorineural hearing loss (60%). ASSR was highly sensitive (85.1%) for estimation of hearing threshold and specificity was 100% (p<0.001). BERA was also highly significant for estimation of hearing threshold (sensitivity: 83%; specificity: 92.3%; p value <0.001). Conclusions: BERA has high degree of accuracy in detecting hearing threshold as an objective test but not as much accurate as ASSR. It is more valuable in terms of identification of site and size of the lesion in auditory pathway and identification for the type of the deafness.